2009
DOI: 10.1002/humu.21094
|View full text |Cite
|
Sign up to set email alerts
|

EYA4, deleted in a case with middle interhemispheric variant of holoprosencephaly, interacts withSIX3both physically and functionally

Abstract: Holoprosencephaly (HPE) is the most common congenital malformation of the developing human forebrain, in which the two cerebral hemispheres fail to separate to various degrees. Although pathological mutations have been identified in up to nine genes, a number of other genes as well as environmental factors are likely to be involved in HPE. Here, we describe a case with the middle interhemispheric variant, a milder variant of HPE, carrying a deletion of ~10.4 Mb at 6q22.31-q23.2, which includes the EYA4 gene. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The importance of maternal contribution of Importin α proteins is plausible, because it is known from Drosophila that the transition from maternal to zygotic control occurs only at cell cycle 13–14 [55,56]. Already before this transition the nuclear import machinery is essential to allow gene activity.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of maternal contribution of Importin α proteins is plausible, because it is known from Drosophila that the transition from maternal to zygotic control occurs only at cell cycle 13–14 [55,56]. Already before this transition the nuclear import machinery is essential to allow gene activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the roles for mammalian Eya2 and Eya3 in craniofacial development have not yet been established, although they are required in other tissues (Grifone et al, 2007; Soker et al, 2008); there also are no reported human defects involving Eya2 or Eya3 to date. Nonetheless, the expression of Eya2 and Eya3 in the Xenopus and chick PPE and placodes, and the demonstrated ability of each of the four vertebrate Eya proteins to interact with Six1, Six2 and/or Six4 (Heanue et al, 1999; Ohto et al, 1999; Ikeda et al, 2002; Li et al, 2003; Schonberger et al, 2005; Abe et al, 2009) predict that all four Eya genes are likely to act as Six gene co-factors, perhaps with redundant roles, during craniofacial development.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Eya4 plays an important role in inner-ear function. A recent study has shown that EYA4 and SIX3 interact both physically and functionally, and both genes have been reported to be mutated in some cases of holoprosencephaly [8385]. …”
Section: Eya and So/six Genes In Vertebrate Development And Diseasementioning
confidence: 99%